Formulation For Resolution of Partial Or Complete Overlapping of Mining Business Permit Areas - Sihaloho, Meylin; Indah Dwi Qurbani; Venny Indria (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
Mineral and coal mining plays a strategic role in national development because it contributes to economic growth, energy security, and increased state revenue. However, this sector still faces serious problems in the form of overlapping Mining Business Permit Areas (WIUP), which give rise to legal uncertainty, conflicts of interest, and inefficient natural resource governance. Overlapping permits arise from a weak licensing administration system, regulatory disharmony, and a lack of coordination between central and regional government agencies. This situation has implications for disrupting the investment climate, declining business confidence, and reducing state revenue from the mining sector. As a normative response, Law Number 2 of 2025, specifically Article 171B, regulates the authority of the Central Government to evaluate and revoke Mining Business Permits (IUP) that experience overlap in part or all of their areas. This policy is a strategic step to reorganize licensing and ensure legal certainty in accordance with the mandate of Article 33 of the 1945 Constitution. However, its implementation faces challenges in the form of limited integrated spatial data, a weak national mining information system, and the absence of a standard mechanism for resolving overlapping permit disputes. This study uses a normative juridical method with a statutory, conceptual, and case approach to analyze the urgency and formulation of regulations for resolving overlapping WIUPs. The results of the study indicate that derivative regulations are needed in the form of comprehensive, systematic, and applicable Government Regulations to regulate the evaluation, revocation, and dispute resolution mechanisms in a transparent manner. Thus, clear and integrated regulations are not only able to create legal certainty and justice, but also ensure the utilization of mineral and coal resources for the greatest prosperity of the people.